Programming the landscape – the objectification of space - Schwartz, Scott (Signs - International Journal of Semiotics, 2012)
The following paper will attempt to illuminate and elaborate on a distinct pattern of human behavior, namely the idea that the collective actions of groups (cultures) are directed toward the objectification of their environments. This paper will attempt to prove that this is indeed the case, and further, explain why and how this behavior is undertaken. The more focused implication of this broad assertion is that groups are motivated to program their landscapes in order to position themselves within a more predictable temporal trajectory. It is the assertion herein that the capacity for symbolic thought is the primary vehicle through which this achieved.